Emotional intelligence as a protective factor of risky driving and road accidents. - Megías-Robles, Alberto; Sánchez-López, María T.; Fernández-Berrocal, Pablo (My University, 2021)
Title: Emotional intelligence as a protective factor of risky driving and road accidents. Authors: Alberto Megías-Robles, María T. Sánchez-López, and Pablo Fernández-Berrocal Department of Basic Psychology, Faculty of Psychology, University of Málaga, Spain. Introduction Deliberate risky behaviours such as speeding, drink-driving, or the non-use of safety measures are one of the main contributing factors to road accidents. The objective of this research was to clarify the relationship between EI abilities, risk-taking while driving, and the potential negative outcomes of these behaviours (road accidents and traffic tickets). Method Five hundred and fifty-five drivers from a Spanish community sample (Mage = 39.34, ranging from 18 to 79 years old; 49.19% women) were assessed on risky driving behaviour and EI by the Dula dangerous driving index and the Wong and Law emotional intelligence scale, respectively. Results The results of the present research revealed that drivers who self-reported good abilities in EI had a lower tendency to risk-taking while driving. Moreover, EI was negatively and indirectly related to the number of road accidents and traffic tickets through the mediating effect of risky driving. Conclusions These findings suggest the involvement of emotional factors, mainly the lack of abilities in recognizing and managing emotions, in the explanation of risky driving behaviour. For instance, a proper management of emotions would allow for coping with anger or stressful traffic situations that might trigger risk behaviours such as speeding or rule violations. Future experimental studies should be aimed to confirm the causal role of EI on risky driving. If so, training programs designed to improve emotional competencies could be a very useful strategy in road safety.
Keywords: Emotional abilities; Driving; Road accidents; Psicología